Conflicts of land tenure and tree tenure on land use and management among agro-based households in Nigeria (2013)
Tenure issues in natural resources management and control limit agricultural enterprise and effective land use. Conflicts arising from land tenure and tree tenure were examined in eight (8) communities across Northern and Southern Nigeria. The research included preliminary surveys, interviews and questionnaires to obtain relevant information on tenure conflict history, agricultural enterprises, resource user groups and rights exercised in land use and management. Root cause analysis was used to identify underlying and immediate causes of tenure conflicts. Furthermore, the intensity of conflict was analysed using resource devolution tool. Results obtained show informal procedural patterns of resource ownership and transfers as key underlying cause in land-tree tenure conflict in the Northern region while appreciation in the resource value was key underlying cause in the Southern region. The conflict situation affected different categories of resource users. In addition, to individualized agro-enterprises modifications among households, there are pluralized enterprise activities: a response to the conflict situation. In both regions, access, withdrawal and management rights had high intensity conflict cases involving mostly small scale farmers, land trustees, land tenants and land owners. Standardized property titling, strengthening of local/customary institutions in alternative dispute resolution and development of flexible tenure system to accommodate resource poor user groups especially in rural areas are salient policy issues that can stem resource conflict incidence.